Kahoot!: Effective, simple and easy gamification in Higher Education: Practical application in an Engineering Degree - González Alcántara, Óscar Jesús; Fontaneda González, Ignacio; Camino López, Miguel Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The European Higher Education Area (EHEA) establishes that learning must be student-centered. Based on this statement, the article explains how gamification can be a pedagogical technique that can provide the desired change in university teaching towards the EHEA patterns. This paper presents the design of a simple and easy to implement gamification methodology in an Engineering Degree using Kahoot! as a tool and its evolution over three academic years. The results indicate that the students find the subject more attractive, its follow-up increases and their academic results improve.